China’s Soft Power to Indonesia: Opportunities and Challenges - Ridha Amalia (Indonesian Journal of International Relations, 2018)
The debate concerning China’s rise usually focused on its economic and military capability. However, the recent trend in International affairs shows that soft power is essential components of Great Power status. As well as China who uses soft power as a tool of its foreign policy in the modern era. One of the countries that are subjected to China’s soft power is Indonesia. Indonesia is important for China because of its role in Association of Southeast Asian Nations (ASEAN) and also its raw commodities that China need. That is why the aim of this essay is to analyze opportunities and challenges for China soft power to Indonesia.